IEC TS 62578: 2015 - Borcherding, Holger
IEC TS 62578:2015 describes the operation conditions and typical characteristics of active infeed converters (AIC) of all technologies and topologies which can be connected between the electrical power supply network (lines) a.c. side and a constant current or voltage type d.c. side and which can convert electrical power (active and reactive) in both directions (generative or regenerative). The following is excluded from the scope: - Requirements for the design, development or further functionality of active infeed applications. - Probability of interactions or influences of the AIC with other equipment caused by parasitic elements in an installation or caused by poor electronic design as well as their mitigations. - 'Overhead line' power supply networks because of lack of information (measurements) of their three phase impedances. This edition includes the following significant technical changes with respect to the previous edition: a) IEC TS 62578, in its revised version includes observed values out of practical applications for emission values below 150 kHz. b) Therefore the document has been extended compared to the first edition, several detailed analysis results are given in the extended Annexes. c) Design recommendations have been derived from the international working group by an assessment of the power supply impedances between 2 kHz and 9 kHz, a comprehensive analysis of the withstand capability of power capacitors against harmonic currents injected by AIC, immunity tests of equipment and considerations about shifted resonances in the power supply network with increased population of undamped filter capacitors.